Effect of psychiatric co-morbidity on adherence to anti tubercular treatment: a cross sectional study from North India - Kaur, Ravdeep; Singh, Tarundeep; Singh, Shubh Mohan; Kumar, Rajesh (International Journal Of Community Medicine And Public Health, 2021)
Background: Study explores relationship between depressive disorder and adherence to DOTS (Directly Observed Therapy Short Course) and whether treatment of depressive disorder according to severity of depressive disorder should be an option to improve adherence to DOTS. Methods: Study included 182 newly diagnosed adult cases of tuberculosis who were on anti- tuberculosis therapy (ATT) as per program guidelines and were in third month under DOTS category I and category II therapy. Patients were screened for depressive and anxiety disorder using PHQ-9 and GAD-7. Modified ACTG baseline questionnaire was used to collect data about adherence and reasons for partial adherence. Results: Overall prevalence of depressive disorder amongst participants was found to be 37.9% and that of partial adherence (missed two or more than two doses) was 12.1%. Partial adherence was mostly seen in the first month, followed by third and second month of DOTS. Twenty- two percent patients with depressive disorder were partially adherent to ATT. Odds ratio suggests higher risk being partially adherent to ATT were greater in the participants who had depressive disorder. Conclusions: This study highlights the benefit of screening patients while diagnosing tuberculosis patients for depressive disorder, to improve disease outcome and reduce likelihood of MDR-TB.